2015
DOI: 10.1111/ijcs.12257
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable clothing: challenges, barriers and interventions for encouraging more sustainable consumer behaviour

Abstract: Research with consumers has revealed limited awareness of the sustainability impact of clothing (Goworek et al., 2012). Semi-structured interviews conducted with a range of experts in sustainable clothing to increase understanding of the challenges for sustainable clothing revealed that a focus on sustainability alone will not drive the necessary changes in consumers' clothing purchase, care and disposal behaviour for three reasons: (i) clothing sustainability is too complex; (ii) consumers are too diverse in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
231
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(250 citation statements)
references
References 40 publications
10
231
4
5
Order By: Relevance
“…One answer has been to encourage consumers to be more environmentally conscious in their consumption. There is extensive research in the field of sustainable consumption, which has many emphases, including voluntary simplification, clothing and food choices (e.g., Carrigan, 2017;Harris, Roby, & Dibb, 2016;Peattie, 2009;Shaw, McMaster, & Newholm, 2016). Focus has primarily been on the sustainable or "ethical" consumers, who are said to have a high level of environmental awareness and concern and consequentially, reportedly alter their consumption behaviours to reduce their impact on the environment (Eckhardt, Belk, & Devinney, 2010;Shaw & Newholm, 2002).…”
Section: Sustainable Consumptionmentioning
confidence: 99%
“…One answer has been to encourage consumers to be more environmentally conscious in their consumption. There is extensive research in the field of sustainable consumption, which has many emphases, including voluntary simplification, clothing and food choices (e.g., Carrigan, 2017;Harris, Roby, & Dibb, 2016;Peattie, 2009;Shaw, McMaster, & Newholm, 2016). Focus has primarily been on the sustainable or "ethical" consumers, who are said to have a high level of environmental awareness and concern and consequentially, reportedly alter their consumption behaviours to reduce their impact on the environment (Eckhardt, Belk, & Devinney, 2010;Shaw & Newholm, 2002).…”
Section: Sustainable Consumptionmentioning
confidence: 99%
“…Harris, Roby, and Dibb () identified the following obstacles to consumer preference for slow fashion products: consumers' lack of knowledge and understanding about sustainability, their ethical concerns on different matters, and thoughts such as “I look good in these clothes,” when their main criterion should be how it is produced. Forsman and Madsen () found that consumers are interested in sustainable fashion, but they also find it “inaccessible” because it is expensive and not accessible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pookulangara and Shephard (2013) conducted focus group interviews and concluded that consumers did not have enough knowledge of slow fashion to make conscious purchasing decisions, and they did not find products in slow fashion suitable for fashion. Harris, Roby, and Dibb (2015) identified the following obstacles to consumer preference for slow fashion products: consumers' lack of knowledge and understanding about sustainability, their ethical concerns on different matters, and thoughts such as "I look good in these clothes," when their main criterion should be how it is produced. Forsman and Madsen (2017) found that consumers are interested in sustainable fashion, but they also find it "inaccessible" because it is expensive and not accessible.…”
Section: Slow Fashionmentioning
confidence: 99%
“…In recent research, scholars have begun to observe and discuss the sector-specific external and internal barriers that confront apparel consumers. They identify factors such as limited knowledge, limited availability of alternative products as well as the role of fashion, societal norms, and status connected with personal visibility, appearance, and style (e.g., Hiller 2010; McNeill and More 2015; Harris et al 2016). Two articles in this special issue offer further insights into why this kind of sustainability mobilization is a particularly tricky task in the field of clothing and textiles and, thus, suggest that too much hope and responsibility is, at least at present, being placed on individual consumers and families.…”
Section: Responsibility For Demand Side Sustainabilitymentioning
confidence: 99%